2008
DOI: 10.1029/2007jb005121
|View full text |Cite
|
Sign up to set email alerts
|

Structure and growth of the Izu‐Bonin‐Mariana arc crust: 2. Role of crust‐mantle transformation and the transparent Moho in arc crust evolution

Abstract: Evolution of arc crust and subarc mantle in the Izu‐Bonin‐Mariana (IBM) intraoceanic arc‐trench system is examined by petrological modeling of arc magma generation and differentiation. Characteristic seismic structural features of the IBM arc highlighted in this modeling include the presence of (1) a middle crust with a P wave velocity (Vp) of 6.0–6.5 km/s, (2) a 6.5–6.8 km/s Vp layer at the top of the lower crust, (3) a high‐velocity (Vp = 6.8–7.2 km/s) lower crust, and (4) an uppermost mantle exhibiting rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(144 citation statements)
references
References 82 publications
5
136
1
2
Order By: Relevance
“…Much of this seems to have disappeared, most likely by foundering into the upper mantle. Tatsumi et al (2008) concluded that middle Izu-Bonin-Mariana arc crust of intermediate composition was generated from mantle-derived basalts via complex multistage magmatic processes. These include anatexis of amphibolite-facies mafic lower crust to generate felsic melts and mixing of felsic melts with mantle-derived basaltic magma ( Figure 6).…”
Section: Lower Crust Founderingmentioning
confidence: 99%
See 3 more Smart Citations
“…Much of this seems to have disappeared, most likely by foundering into the upper mantle. Tatsumi et al (2008) concluded that middle Izu-Bonin-Mariana arc crust of intermediate composition was generated from mantle-derived basalts via complex multistage magmatic processes. These include anatexis of amphibolite-facies mafic lower crust to generate felsic melts and mixing of felsic melts with mantle-derived basaltic magma ( Figure 6).…”
Section: Lower Crust Founderingmentioning
confidence: 99%
“…magmatically adds to pre-existing continental crust, such as that beneath the Andes. Juvenile continental crust is mostly extracted from the mantle as mafic (basaltic or boninitic) magma, which must be further refined by anatectic remelting of the crust and delamination (foundering) to yield andesitic material approximating the bulk composition of continental crust (Rudnick and Gao 2003;Tatsumi 2005;Tatsumi et al 2008). Although juvenile continental crust is likely to be mafic at first, it inherits from subduction zone processes the distinctive geochemical characteristics of subduction-related magmas: enrichment in silica and LIL elements (e.g.…”
Section: Crust Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…The origin of I-type granitoids in arcs is very much discussed, and proposed models can be grouped in two endmember processes: partial melting of amphibolites in the lower arc crust (e.g., Clemens 1990;Clemens and Vielzeuf 1987;Tatsumi et al 2008Tatsumi et al , 2009 or hydrous high-to medium-pressure magma differentiation with limited amount of assimilation in the lower crust (e.g., Davidson et al 2007;Jagoutz et al 2009;Sisson et al 2005). We have previously discussed the origin of the Kohistan arc granitoids based on a more limited dataset and from the perspective of processes in the lower arc crust exposed in the Southern Plutonic Complex and the Chilas Complex (Jagoutz 2010;Jagoutz et al 2009Jagoutz et al , 2011.…”
Section: Origin Of the Kohistan Batholith Granitoidsmentioning
confidence: 99%